STRATEGI PENINGKATAN KETAATAN PELAKU USAHA UDANG VANAME (Litopenaeus Vannamei) BERBASIS RISIKO SEKTOR KELAUTAN DAN PERIKANAN STUDI KASUS DI KABUPATEN PANDEGLANG, BANTEN - Meisyaputra, Adhie; Nainggolan, Armen; Lestira Dhewantara, Yudha (Fakultas Perikanan dan Ilmu Kelautan Universitas Satya Negara Indonesia, 2023)
The purpose of this study was to determine the level of obedience of vannamei shrimp growers in Pandeglang Regency, Banten. The aim is to increase the compliance of vannamei shrimp businesses with applicable laws and regulations. Data analysis, to determine the level of obedience of aquaculture business actors, is carried out descriptive analysis, as well as to develop strategies to increase the compliance of aquaculture business actors with applicable laws and regulations, carried out using the AHP (Analytical Hierarchy Process) method using 3 (three) people experts from regulators, academics, law enforcement. The results of the study, the level of compliance of vannamei shrimp enlargement business actors in fulfilling licensing documents for aquaculture business actors, there are 9 (nine) business actors who have met the standard, 6 (six) business actors still need improvement, especially in fulfilling the compliance CBIB technical requirements. The most important strategic priority in increasing the obedience of business actors is to increase the number of Fisheries Supervision Personnel 0.4210, simplify the bureaucracy 0.2927, Assistance by Fisheries Extension 0.2862.